World Café method integrated with QFD for obtaining the Voice of the Customer - Torres,Jair Gustavo de Mello (2018)
Abstract Paper aims Investigate the results of the use of the World Café method as a tool to assist the capture of the Voice of the Customer, in a curricular discipline that works with ABPj (Project-Based Learning). Originality As the authors have not found in the literature the application of the World Café method integrated to QFD. Research method Teachers and the coordination of a Logistics course worked together on the application of the method, following the five major phases of the action research, which are: diagnosis, planning, action, evaluation and learning. Main findings The method allowed to establish the most important personal characteristics needed to develop the pedagogical projects, from the point of view of the students. Implications for theory and practice The findings of this work can be used as a basis to understand how to engage students in pedagogical logistics projects.